Governing common-properties of low-cost flats in Selangor: issues and challenges - Wang, Hong Kok (2013)

(untitled)
Hardin’s (1968) seminal paper “The tragedy of the commons” has generated so much attention on common-pool resource (CPR) management and whose findings are still valid today shows the inadequacy of human nature in dealing with collective action, and the unique nature of “public goods” that few policy makers appreciate. In Malaysia, the social phenomenon where many common-areas of strata buildings are badly managed by developers/ property management companies/ parcel holders under the existing institutional arrangements of self-governance, lends credence to Hardin’s (1968) allegory. The research explored the contributing factors that make self-governance such a challenge where the maintenance of the common-areas is outside the state government purview. In this endeavour, a mixed methods approach was employed using institutional analysis development (IAD) framework as the main theoretical framework, and new institutional economics (NIE) reasoning as rival theories. Three qualitative studies that were conducted on four low-cost housing as recommended by the Selangor State Housing Board, provided insight into the varying degrees of success of self-governance: a phenomenological study; a narrative study; and a multi-case study. In the quantitative phase, a survey research was conducted on a sample of 633 respondents from a total population of 1,598 households. Three statistical procedures were later performed to explore the determinants, the inter-group membership differences, and the intra-group membership differences that shaped the state of health of the commons. The study lent weight to the notion that a community with higher social capital tended to produce higher collective action (users’ characteristics). But cultural factor which was part of an endogenous institution that shaped human conduct in daily settings had a role, as relying on court ordering was costly and cumbersome (rulesin- use). In a common area, the challenge had been on how to discourage free-riding habits of parcel holders (the nature of material condition). A more transparent style of governance certainly helped). The endemic failure of the institution of self-governance in any low-cost housing in Malaysia is similar to any CPR management of natural resource in every corner of the world. The study concluded that the root cause is failure to appreciate the basic human nature of “methodological individualism and instrumental rationality”, and the nature of the commons as “public goods”. Every man is rational only in making his private decision for private goods and the dominant strategy in using public goods is to free-ride. The study recommended state intervention as parcel holders were incapable to fend for themselves, though there is likelihood that state-led governance may not deliver the result as envisaged.